The end of normal identity in a biocultural era - Davis, Lennard J. 1949- (Univ. of Michigan Press, 2013)
"In an era when human lives are increasingly measured and weighed in relation to the medical and scientific, notions of what is "normal" have changed drastically. While it is no longer useful to think of a person's particular race, gender, sexual orientation, or choice as "normal," the concept continues to haunt us in other ways. In The End of Normal, Lennard J. Davis explores changing perceptions of body and mind in social, cultural, and political life as the 21st century unfolds. The book's provocative essays mine the worlds of advertising, film, literature, and the visual arts as they consider issues of disability, depression, physician-assisted suicide, medical diagnosis, transgender, and other identities. Using contemporary discussions of biopower and biopolitics, Davis focuses on social and cultural production...particularly on issues around the different body and mind. The End of Normal seeks an analysis that works comfortably in the intersection between science, medicine, technology, and culture, and will appeal to those interested in cultural studies, bodily practices, disability, science and medical studies, feminist materialism, psychiatry, and psychology"..